Nanoparticle-Enhanced Engine Oils for Automotive Applications: Thermal Conductivity and Heat Capacity Improvements - G. D. C. P. Galpaya; M. D. K. M. Gunasena; D. K. A. Induranga; H. V. V. Priyadarshana; S. V. A. A. Indupama; E. R. J. M. D. D. P. Wijesekara; M. I. Ishra; M. M. M. G. P. G. Mantilaka; K. R. Koswattage (Molecules)
The poor thermal and physical properties of conventional engine oils limit vehicle performance and durability. This research aims to investigate the effect of nanoparticles such as fullerene C60, titanium dioxide (TiO2), iron oxide (Fe2O3), and reduced graphene oxide (rGO) nanoparticles on 10W30 Mobil engine oil. In this study, the effect of nanoparticle concentrations at different mass fractions (0.01, 0.05, and 0.1) was examined within the temperature range 30–120 °C. The nanofluids were prepared using a two-step direct mixing method and thermal properties were measured using a LAMBDA thermal conductivity meter, which uses the transient hot wire method according to the ISO standards. Due to the low concentrations of the nanofluids, surfactants were not required at all, and the stability of the nanofluids was visually monitored over a period of four weeks. Accordingly, the largest improvement in thermal conductivity occurred with TiO2/10W30 at a mass fraction of 0.1 wt.% at 80 °C, and the specific heat capacity improved due to Fe2O3/10W30 addition at a mass fraction of 0.1 at 70 °C; these were 5.8% and 14.4%, respectively, for the base oil. Thermal diffusivity remained largely unaffected by the addition of the nanoparticles, and fullerene C60 showed no significant effect on any thermal property. It was concluded that the thermal properties of the engine oil were considerably enhanced by the added nanoparticles at different weight fractions and temperature values.